Subject trend analysis of theses submitted to the U.P. Institute of Library and Information Science, 1981-2000 - Gapas, Amor C.; Dela Torre, Nathalie N. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study was conducted to find out the current trend in library science research submitted to the U.P. Institute of Library and Information Science in terms of topics chosen for study. The study covered a total of 378 theses, both of undergraduates and graduate students, from 1981 to 2000. The researcher employed simple statistics and tabulation in the presentation and analysis of data.
Study revealed that both Library Use and Users and Libraries and Resource Centers got the most number of research outputs. Most of the research under these categories focused on user studies and evaluative survey studies. The second most popular is the Profession, which focused on studies about library and information staff; third is Bibliographic control, which emphasized greatly on bibliography and bibliographical issues; fourth is Communications and Information Technology that dealt mostly on computer applications; and the fifth most popular is Organization category, bulk of which is about cooperation among libraries.
The least five subject areas were also identified. Among these is Librarianship and Information Science as the very least studied subject; next is Media and Library Buildings; third is Bibliographic control and Archival Management; Computerized Information Storage and Retrieval and Records Management tied at fourth; and fifth is Technical Services. There were less than ten research produced under each of these categories for the past 20 years. Meanwhile, it is worth mentioning that Information Communication, Materials, and most especially LIS education showed a great potential in producing more studies in the future.
The following recommendations were formulated in the light of the initial findings of the study: (a) that more studies should be encouraged for both the least and promising subjects through continued improvement of the LIS curriculum; (b)that faculties, based on their specialization, submit lists of topics for possible research, as a guide for future researchers; and (c) that further studies like this, within and among library science schools, be conducted every period of 5 to 10 years so that future researchers can come up with relevant and quality outputs.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Institute of Library and Information Science -- Dissertations, Academic -- Philippines -- Quezon City; Library science -- Research -- Philippines -- Quezon City